WORKSHOP FORMULATION OF LIQUID SOAP PREPARATIONS OF CITRUS LEAF EXTRACT PURUT (CITRUS HYSTRIX) AS AN ANTISEPTIC AGAINST STAPHYLOCOCCUS AUREUS BACTERIA: WORKSHOP FORMULATION OF LIQUID SOAP PREPARATIONS OF CITRUS LEAF EXTRACT PURUT (CITRUS HYSTRIX) AS AN ANTISEPTIC AGAINST STAPHYLOCOCCUS AUREUS BACTERIA - pratiwi, asti; Siahaan, Safrika Juliana; Pranata, Chandra; Darmirani, Yosi (JURNAL PENGMAS KESTRA (JPK), 2022)
Kaffir lime leaves contain compounds such as flavonoids, saponins, and tannins. Staphylococcus aureus is a pathogenic bacterium associated with virulence. Pharmaceutical preparations used to maintain healthy skin are soaps. The purpose of this study was to determine the inhibitory power of the Liquid Soap Preparation Formulation of Kaffir lime Leaf Extract as an Antiseptic Against Staphylococcus aureus Bacteria. The study was carried out by making ethanol extract of purut orange leaves formulated with liquid soap preparations, then an inhibitory test was carried out on Staphylococcus aureus bacteria that had been bred 3 times with concentrations of 20%, 40%, and 60% and positive and negative controls were carried out. The results of the analysis showed that the formulation of liquid soap preparations of ethanol extract of purut orange leaves with a concentration of 60% has the strongest power against the growth of Staphylococcus aureus bacteria. In conclusion, the concentration of the formulation of liquid soap preparations of ethanol extract of purut orange leaves is directly proportional to the magnitude of the diameter of the inhibitory zone.